Decreased Fitness and Virulence in ST10 Escherichia coli Harboring blaNDM-5 and mcr-1 against a ST4981 Strain with blaNDM-5 - Zhang, Yawei; Liao, Kang; Gao, Hua; Wang, Qi; Wang, Xiaojuan; Li, Henan; Wang, Ruobing; Wang, Hui (Frontiers in Cellular and Infection Microbiology, 2017)
Although coexistence of blaNDM-5 and mcr-1 in Escherichia coli has been reported, little is known about the fitness and virulence of such strains. Three carbapenem-resistant Escherichia coli (GZ1, GZ2 and GZ3) successively isolated from one patient in 2015 were investigated for microbiological fitness and virulence. GZ1 and GZ2 were also resistant to colistin. To verify the association between plasmids and fitness, growth kinetics of the transconjugants were performed. We also analyzed genomic sequences of GZ2 and GZ3 using PacBio sequencing. GZ1 and GZ2 (ST10) co-harbored blaNDM-5 and mcr-1, while GZ3 (ST4981) carried only blaNDM-5. GZ3 demonstrated significantly more rapid growth (P<0.001) and overgrew GZ2 with a competitive index of 1.0157 (4 h) and 2.5207 (24 h). Increased resistance to serum killing and mice mortality was also identified in GZ3. While GZ2 had four plasmids (IncI2, IncX3, IncHI2, IncFII), GZ3 possessed one plasmid (IncFII). The genetic contexts of blaNDM-5 in GZ2 and GZ3 were identical but inserted into different backbones, IncX3 (102,512 bp) and IncFII (91,451 bp), respectively. The growth was not statistically different between the transconjugants with mcr-1 or blaNDM-5 plasmid and recipient (P=0.6238). Whole genome sequence analysis revealed that 28 virulence genes were specific to GZ3, potentially contributing to increased virulence of GZ3. Decreased fitness and virulence in a mcr-1 and blaNDM-5 co-harboring ST10 E. coli was found alongside a ST4981 strain with only blaNDM-5. Acquisition of mcr-1 or blaNDM-5 plasmid did not lead to considerable fitness costs, indicating the potential for dissemination of mcr-1 and blaNDM-5 in Enterobacteriaceae.